The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep45356
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related alterations of gut microbiota composition in the BTBR mouse model of autism spectrum disorder

Abstract: Alterations of microbiota-gut-brain axis have been invoked in the pathogenesis of autism spectrum disorders (ASD). Mouse models could represent an excellent tool to understand how gut dysbiosis and related alterations may contribute to autistic phenotype. In this study we paralleled gut microbiota (GM) profiles, behavioral characteristics, intestinal integrity and immunological features of colon tissues in BTBR T + tf/J (BTBR) inbred mice, a well established animal model of ASD. Sex differences, up to date poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 48 publications
(60 reference statements)
8
108
1
1
Order By: Relevance
“…In addition, we found that this early life exposure affects cortical 5HT metabolism, elevated markers of neuroinflammation, and oxytocin, as well as corticosterone levels in response to social interaction. This constellation of changes reflects neurobiological changes seen in individuals with ASD [9,31,42,43,5052]. Our findings suggest that the roots of the psychopathology of this disorder may lie in utero, and be connected to aberrant establishment of the Gut-brain-axis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, we found that this early life exposure affects cortical 5HT metabolism, elevated markers of neuroinflammation, and oxytocin, as well as corticosterone levels in response to social interaction. This constellation of changes reflects neurobiological changes seen in individuals with ASD [9,31,42,43,5052]. Our findings suggest that the roots of the psychopathology of this disorder may lie in utero, and be connected to aberrant establishment of the Gut-brain-axis.…”
Section: Discussionmentioning
confidence: 51%
“…We previously have demonstrated a significant reduction in Bacteriodes in males exposed to restraint stress and a social defeat stressor, and significantly increased circulating levels of IL-6 and CCL2 [18] [Bailey et al, unpublished observation]. Of note, a recent study has linked Bacteroides and Parabacteroides , along with a number of other microbes, to contributing to sex-specific changes in behavior in a mouse model of autism [50]. In addition, treatment with Bacteroides fragilis was able to ameliorate the behavioral and inflammatory abnormalities in the maternal immune activation (MIA) model of autism [10].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some groups have found immune-related phenotypes in females only. For example, the BTBR mouse model of ASD exhibited female-specific increases in self-grooming behavior, and levels of IL-6 and CD11c [131]. At 6 weeks, wildtype mice prenatally treated with Poly I:C had decreased DNA methylation globally, particularly in females, and decreased methylation at the promoter region of MeCP2, a gene associated with ND [132].…”
Section: Can Immune Activation Lead To Sex-biased Diagnoses?mentioning
confidence: 99%
“…Gene sequencing analyses by Foley, MacFabe, Kavaliers, and Ossenkopp (2015) revealed that infants with ASD have a higher abundance of bacterial genera Faecalibacterium, and lower levels of Blautia, in fecal and blood samples. Recently, a study by Coretti et al (2017) on mice models have elucidated markedly unique microbial and immune profiles in male and female autistic mice, suggesting the possible role of the microbiota in influencing sex-specific susceptibility to autism.…”
mentioning
confidence: 99%